Diversity, distribution and different habitat use among the tropical freshwater eels of genus Anguilla - Takaomi Arai (Nature Portfolio, 2017)
Abstract Along with the mysteries of their ecology, freshwater eels have fascinated biologists for centuries. However, information concerning species diversity, geographic distribution, and life histories of the tropical anguillid eels in the Indo-Pacific region are highly limited. Comprehensive research on the species composition, distribution and habitat use among tropical anguillid eels in the Peninsular Malaysia were conducted for four years. A total of 463 specimens were collected in the northwestern peninsular area. The dominant species was A. bicolor bicolor constituting of 88.1% of the total eels, the second one was A. bengalensis bengalensis at 11.7%, while A. marmorata was the least abundant at 0.2%. A. bicolor bicolor was widely distributed from upstream to downstream areas of the rivers. In comparison, A. bengalensis bengalensis preferred to reside from the upstream to midstream areas with no tidal zones, cooler water temperatures and higher elevation areas. The habitat preference might be different between sites due to inter-species interactions and intra-specific plasticity to local environmental conditions. These results suggest that habitat use in the tropical anguillid eels might be more influenced by ambient environmental factors, such as salinity, temperature, elevation, river size and carrying capacity, than ecological competition, such as interspecific competition.